2014
DOI: 10.1177/1741143213510509
|View full text |Cite
|
Sign up to set email alerts
|

Are School Boards aware of the educational quality of their schools?

Abstract: School boards are expected to monitor and enhance the educational quality of their schools. To know whether and how school boards are able to do so, we first of all need to know whether school boards are aware of the educational quality of their schools in the first place. Taking Dutch school boards in primary education as an exemplary case ( N = 332) we developed and tested a path model using structural equation modelling to analyse the extent to which school boards discern educational quality in their school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 25 publications
0
40
0
2
Order By: Relevance
“…A first issue is the ambiguous attitude adopted by the government toward schools in the form of continually encouraging increased autonomy while simultaneously restricting educational freedom with the introduction of new rules. The pressure imposed by external regulation and accounting is at odds with the internal desire of schools to pay attention to predominantly the realization high quality of education (Hooge & Honingh, 2014). Stated differently, the inspectorate should attend to not only the monitoring of schools to promote optimal performance but also the stimulation of quality development (Gaertner, 2013).…”
Section: Towards Shared Monitoring Of the Quality Of Education In Thementioning
confidence: 99%
“…A first issue is the ambiguous attitude adopted by the government toward schools in the form of continually encouraging increased autonomy while simultaneously restricting educational freedom with the introduction of new rules. The pressure imposed by external regulation and accounting is at odds with the internal desire of schools to pay attention to predominantly the realization high quality of education (Hooge & Honingh, 2014). Stated differently, the inspectorate should attend to not only the monitoring of schools to promote optimal performance but also the stimulation of quality development (Gaertner, 2013).…”
Section: Towards Shared Monitoring Of the Quality Of Education In Thementioning
confidence: 99%
“…Hooge and Honingh (2014) found that school boards have a better picture of school quality when they stick to their governing role and when school leaders stick to their management role. Tension seems to occur when roles are unclear, or when boards and leaders have different perception of their respective roles (Hooge and Honingh, 2014). For inquiry-based working this means that school boards can set out a policy and vision for inquiry-based working and delegate the responsibly of creating a culture of inquiry in schools to school leaders and their teachers.…”
Section: The Crucial Role Of the School Leadermentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa mutu pendidikan dipengaruhi oleh infrastruktur sekolah, keterlibatan orang tua dan penggunaan teknologi dalam pendidikan (Albaker, 2017). Penelitian lain juga menunjukkan adanya peran dewan sekolah dan pihak pengelola sekolah dalam pengendalian mutu (Hooge & Honingh, 2014). Sedangkan penelitian di Brazil menunjukkan bahwa organisasi internasional juga berperan dalam penjaminan mutu sekolah.…”
Section: Pendahuluanunclassified